O colecionador de palavras: o projeto dicionarístico de Luís da Câmara Cascudo - Maciel, Raquel Silva (2024)
In 1943, at the invitation of Augusto Meyer, then director of the Instituto Nacional do Livro (INL), the project of publishing a lexicographical writing emerged, which aimed to put the folkloric world in alphabetical order, covering themes related to national culture and inspired by the plan of the Enciclopédia Brasileira. This event benefited from the process of intensification of the production of Brazilian dictionaries that occurred throughout the twentieth century, which, in turn, is due, among other issues, to the development of institutional conditions such as a publishing market accessible to the production of lexicographic texts of national character. In this context, Luís da Câmara Cascudo strives to improve the drafts of his folkloric research, accumulated since the publication of Vaqueiros e Cantadores (1939), and to correspond with intellectuals located in various regions of the country and abroad, requesting the sending of books, documents, photographs and other elements that helped him in the composition of the entries in the Dicionário do Folclore Brasileiro (1954). The problematization of Luís da Câmara Cascudo's dictionary project aims at the development of a discursive analysis of the historical conditions that enabled the emergence of this subject as an alleged interpreter of Brazil, and the construction of a narrative that instituted ways of seeing and saying what is popular and national. Considering this, the discourses and power relations that comprise this production are questioned, based on: research of the networks of sociability, through which he could construct himself as an author and as an intellectual authorized to create narratives about popular culture and, consequently, to construct a discourse of authority about the folkloric element; inquiry regarding their insertion in the development of a national identity project, with a view to the association of folklorists with the State through collaboration in projects for the preservation and constitution of a cultural identity; and investigation of his writing and research practices, paying attention to the realization of a method of folkloric interpretation conceived from different stages - collection, confrontation and origin research - as well as the dialogue he establishes with the folkloric movements. In addition, it apprehends the unfolding of such problematizations, such as the questioning about the author-function, the characterization of the lexicographic subject and the classification of the dictionary product.